Increasing Achievement in Learning Akidah Moral Material on Fatimah Az-Zahra's Exemplary Story Using Videos and Class XI Science Stadium at Ma Luqmanul Hakim Academic Year 2023/2024 - Jajang Rustandi; Marliat; Eka Mustika Riantina (Journal of Educational Analytics, 2023)
The aim of this research is to stimulate children's curiosity about learning. Qualitative descriptive research is this type of research. A number of MA students, madrasa heads and their deputies, as well as an Islamic religious education teacher were the data sources. Luqmanul Hakim. Three Three techniques are used to collect information: documentation, interviews, and observation. Video Content Selection Research Findings. Among the data sources are Relevant. Choose videos or animations that are high quality and relevant to the material about Fatima Az-Zahra's Exemplary Story. The video should depict exemplary values, character and actions that students can take as an example. (1) STAD Group Arrangement Divide students into heterogeneous STAD groups. (2) Introduction with a light discussion. Start with a light discussion session on the theme of Fatima Az-Zahra before showing the video. (3) Video Screening and Post-Show Discussion Play the selected video and make sure students pay close attention. (4) Collaborative Activities in STAD Groups After discussion, give assignments to each STAD group.